Campur Kode Dan Fungsinya Dalam Komunitas Pemain Mobile Legend Bang Bang: Kajian Etno Sosiopragmatik - Martua Reynhat Sitanggang Gusar; Kaleb E. Simanungkalit (Jayapangus Press, 2021)
The aimed of this research is to describe the code writing & the function in the community of Mobile Legend Bang Bang players and the specific terms which are used of that community, especially found at Pasar Baru, Sibuntuon Parpea Villages Lintongnihuta subdistrict. An ethno sociopragmatic approach was used to analyze the data related to code writing, the function of code writing & special terms which users of the community Mobile Legend Player in the Subdistrict mentioned. Collecting the data Conducted with the technique of observation & interview. The result of the research found about 43 special terms that used of Batak Toba Language Speaker. The phenomenon of that code writing happened about the factor of limitation by using code of the speaker Which is as the users of BBT so that if it is used Batak Toba Language because less of efficient. This Phenomenon Finally affected their Communication in the real life. So, the function of code writing in this phenomenon is to optimize and to affect the use of Vocabularies in the Batak Toba Language.